Non‐adaptive phenotypic plasticity: the effects of terrestrial and aquatic herbicides on larval salamander morphology and swim speed. (28th January 2016) - Levis, Nicholas A.; Schooler, Mitchell L.; Johnson, Jarrett R.; Collyer, Michael L.
Abstract : Phenotypic plasticity, although ubiquitous, may not always be advantageous. Non‐adaptive plasticity is likely to occur in response to novel environmental stress. Anthropogenic contaminants, such as herbicides, are novel stressors that are not present in the evolutionary history of most species. We investigated the pattern and consequences of phenotypic plasticity induced by four glyphosate‐based herbicides (two terrestrial and two aquatic) in larvae of the spotted salamander, Ambystoma maculatum, by determining (1) whether the herbicides induced different morphologies; (2) if different morphologies translated to differences in burst swim performance; and (3) how induced individuals performed relative to non‐induced controls. Different herbicide formulations led to the production of significantly different head and tail morphologies, and tail morphology correlated with fastest escape speed. However, escape speed did not vary among treatments. In addition, three out of four herbicide treatments experienced accelerated growth rates, in terms of the lateral size of tails, although the tail shapes were either similar to preliminary controls or intermediate between preliminary and final controls. These observations suggest that herbicide‐induced morphology is a case of non‐adaptive phenotypic plasticity, and that there is potentially a trade‐off between growth and development for larvae exposed to different formulations. Understanding the functional significance of induced phenotypes is important for determining their importance in shaping an organism's ecological interactions and evolutionary trajectories. Furthermore, under different conditions, the morphological changes that we observed in response to exposure to herbicides might affect salamander fitness and influence population dynamics.